PAIN EVALUATION IN WOMEN WITH CERVICALUTERINE NEOPLASMS DURING BRACHYTHERAPY. - Rosa, Luciana Martins da; Lunardi, Fernanda; Hames, Maria Eduarda; Miranda, Gisele Martins; Santos, Maristela Jeci dos; Arzuaga-Salazar, María Angélica (Cogitare Enfermagem, 2022)
Objective: to evaluate pain intensity in women undergoing pelvic brachytherapy. Method: crosssectional, analytical, quantitative study conducted in an oncology institution (Santa Catarina/Brazil), including 97 women undergoing pelvic brachytherapy, with (group 1) or without (group 2) anesthetic sedation. Data collection between September 2018 to July 2019, by structured interview and in the patient's medical record. Pain intensity assessed at five time points by visual analog scale. Analysis included frequency measures, chi-square test, adjusted standardized residuals analysis, generalized estimating equations, Bonferroni post-hoc test; significance level 0.05. Results: 51 women (52.6%) reported pain before brachytherapy, 73 (75.3%) after. At the removal of the applicators, group 1 reached 55.9% in the proportion of presence of pain, group 2, 36.8%. There was significance of pain perception by moment/sedation (p<0.001). Conclusion: pain perception observed in most women. The results contributed to revision of the institutional protocol for intravenous sedation and better pain control.